From Bombing to Targeted Killings: Transformations of the US Fighting Against Global Terrorism - Jan Eichler; Kristýna Stejskalová (Vojenské rozhledy, 2017)
The aim of the article is to compare foreign policy of G. W. Bush jr. and Barack Obama in terms of use of military force. Transition from ground operations to targeted killings is demonstrated on three military operations – Operation Enduring Freedom, Operation Iraqi Freedom and Operation Inherent Resolve. The shift from bombers to drones had several reasons, mainly changing features of the threat. Authors are asking questions why and how did change the US fight against global terrorism with respect to military technologies and how is this change reflected in US fight against the threat of Islamic state.